A COMPARISON BETWEEN GAMES AND GRAMMAR TRANSLATION METHODS IN IMPROVING PUPILS' VOCABULARY ACHIEVEMENT - Sri Yuliana Pandensolang; Nelson B. Panjaitan (Journal of Language Pedagogy, 2011)
In teaching English, the teaching method determine the improvement of vocabularyachievement. Therefore, this study titled "A comparison between Games and GrammarTranslation Methods in improving pupils' Vocabulary Achievement." The participantsinvolved in this study were 62 grade 5 pupils of SDN Karyawangi Parongpong, Bandung.The grade SB composed of 29 pupils, while the grade SC composed of 33 pupils. This studywas divided into three steps: (1) the pretest, (2) the implementation of Games and GrammarTranslation Method (GTM). (3) and the posttest. In the pretest and posttest, the multiplechoice and essays form was administered to them. As the treatment, the researcher taughtGames to one group, and GTM to the other group. At the end of the study, the result provedthat the vocabulary achievement of the pupils taught using Grammar Translation Method ishigher compared to those taught by Games.